Effectiveness of Topical Tranexamic Acid in the Treatment of Melasma - Pandanwangi, Siti; Setriyadi, Dedy; Dzulhijjah, Hawa (Newinera Publisher, 2025)
Melasma is a chronic skin hyperpigmentation condition that often occurs in women of reproductive age, especially in areas exposed to sunlight. One of the therapeutic agents that has attracted attention is tranexamic acid (TXA), which was originally used as an antifibrinolytic agent, but is now known to have an effective mechanism of action in reducing hyperpigmentation. TXA works through plasminogen inhibition, tyrosinase activity, and angiogenesis, as well as providing anti-inflammatory effects. This study uses the PRISMA systematic review method, involving the analysis of 30 relevant articles out of a total of 289 articles identified. The results showed that topical TXA in various formulations, such as creams, gels, or liposomal serums, provided a significant reduction in the Melasma Area and Severity Index (MASI) score. The combination of TXA with other modalities, such as microneedling, laser, and vitamin C, showed more effective results than monotherapy. Topical TXA is an effective and safe therapeutic agent for melasma, especially in the case of refractory or combination therapies. Further research is needed to evaluate the long-term effectiveness and innovation of new formulations in improving the penetration and efficacy of TXA.